Real time monitoring of Staphylococcus aureus biofilm sensitivity towards antibiotics with isothermal microcalorimetry - Sultan, Andi Rofian; Tavakol, Mehri; Lemmens-den Toom, Nicole A.; Croughs, Peter D.; Verkaik, Nelianne J.; Verbon, Annelies; van Wamel, Willem J. B. (PloS one, 2022)
Biofilm-associated infections with Staphylococcus aureus are difficult to treat even after administration of antibiotics that according to the standard susceptibility assays are effective. Currently, the assays used in the clinical laboratories to determine the sensitivity of S . aureus towards antibiotics are not representing the behaviour of biofilm-associated S . aureus , since these assays are performed on planktonic bacteria. In research settings, microcalorimetry has been used for antibiotic susceptibility studies. Therefore, in this study we investigated if we can use isothermal microcalorimetry to monitor the response of biofilm towards antibiotic treatment in real-time. We developed a reproducible method to generate biofilm in an isothermal microcalorimeter setup. Using this system, the sensitivity of 5 methicillin-sensitive S . aureus (MSSA) and 5 methicillin-resistant S . aureus (MRSA) strains from different genetic lineages were determined towards: flucloxacillin, cefuroxime, cefotaxime, gentamicin, rifampicin, vancomycin, levofloxacin, clindamycin, erythromycin, linezolid, fusidic acid, co-trimoxazole, and doxycycline. In contrast to conventional assays, our calorimetry-based biofilm susceptibility assay showed that S . aureus biofilms, regardless MSSA or MRSA, can survive the exposure to the maximum serum concentration of all tested antibiotics. The only treatment with a single antibiotic showing a significant reduction in biofilm survival was rifampicin, yet in 20% of the strains, emerging antibiotic resistance was observed. Furthermore, the combination of rifampicin with flucloxacillin, vancomycin or levofloxacin was able to prevent S . aureus biofilm from becoming resistant to rifampicin. Isothermal microcalorimetry allows real-time monitoring of the sensitivity of S . aureus biofilms towards antibiotics in a fast and reliable way.